(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
COVID-19 is a global pandemic that requires a global response, with a clear need for African involvement. Meaningful participation in global initiatives supports local knowledge-based opportunities for African researchers, builds local capacity and brings research in-house. However, the historical exploitation of vulnerable population groups within South Africa (SA) have given rise to legitimate ethical concerns including mistrust by communities when international transfers of samples and data are contemplated. Historical, cultural and ethical considerations have informed the development of regulations that apply to genomic research in many African jurisdictions. On 1 July 2020, SA’s Protection of Personal Information Act No 4 of 2013 (POPIA) came into force, during an exponential rise of COVID-19 cases. Amid this evolving regulatory landscape, it is unclear what impact the South African regulatory framework will have on international sample and data sharing.